Estudo do efeito do inibidor da enzima adenosina desaminase, EHNA, sobre a enterite induzida pela toxina a do Clostridium difficile em alça ileal isolada de camundongos - Junqueira, Ana Flávia Torquato de Araújo (2008)
The main factor of virulence in Clostridium difficile is toxin A (TxA), which can induce inflammation and acute tissue injury in the bowels of animals and humans affected by this organism. The high concentration of adenosine generated upon injury produces a number of antiinflammatory effects limited by rapid degradation by adenosine deaminase. The objective of this study was to determine the effect of EHNA (erythro-9-(2-hydroxy-3-nonyl)-adenine) inhibition of adenosine deaminase upon TxA-induced ileal loop enteritis in mice. EHNA (90 μmol/kg) or PBS was injected i.p. 30 minutes prior to TxA (10-100 μg) or PBS instillation into the ligated ileal loop. The animals were euthanized 3 hours after enteritis induction and the ileal loops were retrieved for analysis. The weight/length ratio and the secretion volume/length ratio were calculated and tissue samples were submitted to histopathological study, myeloperoxidase assay (MPO), measurement of TNF-α, IL-1β and IL-10 levels with ELISA, immunohistochemical tests for TNF-α, IL-1β, inducible NOS and PTX3, and PCR assay for TNF-α, IL-1β and PTX3. The instillation of TxA (10-100 μg) into the ileal loop significantly increased (p<0.05) the weight/length ratio and the secretion volume/length ratio with consistent results above 50 μg. TxA induced a significant amount (p<0.05) of histological damage, edema and inflammatory cell infiltration and increased the production of TNF-α, IL-1β, iNOS and PTX3. All changes were significantly reverted by treatment with EHNA (p<0.05). Moreover, IL-10 levels remained unchanged in animals treated with TxA, but increased in animals receiving EHNA. In conclusion, in mice with TxA-induced enteritis EHNA produced considerable antiinflammatory effects, reducing tissue injury, neutrophil migration, the expression and levels of proinflammatory cytokines (TNF-α and IL-1β) and producing an increase in IL-10 levels. In addition, TxA instillation increased PTX3 expression and the number of cells immunolabeled for iNOS in the ileal tissue, both of which were reverted by EHNA.